Approximating Iterations for Nonexpansive and Maximal Monotone Operators. (27th August 2015) - Yao, Zhangsong; Cho, Sun Young; Kang, Shin Min; Zhu, Li-Jun
Abstract : We present two algorithms for finding a zero of the sum of two monotone operators and a fixed point of a nonexpansive operator in Hilbert spaces. We show that these two algorithms converge strongly to the minimum norm common element of the zero of the sum of two monotone operators and the fixed point of a nonexpansive operator.